Autoantibodies against central nervous system antigens in a subset of B cell-dominant multiple sclerosis patients - Kürten, Stefanie; Lanz, Tobias; Lingampalli, Nithya; Lahey, Lauren J.; Kleinschnitz, Christoph; Mäurer, Mathias; Schroeter, Michael; Braune, Stefan; Ziemssen, Tjalf; Ho, Peggy P.; Robinson, William H.; Steinman, Lawrence (Proceedings of the National Academy of Sciences of the United States of America, 2020)
Multiple sclerosis (MS) is a chronic autoimmune disease of the central nervous system (CNS), with characteristic inflammatory lesions and demyelination. The clinical benefit of cell-depleting therapies targeting CD20 has emphasized the role of B cells and autoantibodies in MS pathogenesis. We previously introduced an enzyme-linked immunospot spot (ELISpot)-based assay to measure CNS antigen-specific B cells in the blood of MS patients and demonstrated its usefulness as a predictive biomarker for disease activity in measuring the successful outcome of disease-modifying therapies (DMTs). Here we used a planar protein array to investigate CNS-reactive antibodies in the serum of MS patients as well as in B cell culture supernatants after polyclonal stimulation. Anti-CNS antibody reactivity was evident in the sera of the MS cohort, and the antibodies bound a heterogeneous set of molecules, including myelin, axonal cytoskeleton, and ion channel antigens, in individual patients. Immunoglobulin reactivity in supernatants of stimulated B cells was directed against a broad range of CNS antigens. A group of MS patients with a highly active B cell component was identified by the ELISpot assay. Those antibody reactivities remained stable over time. These assays with protein arrays identify MS patients with a highly active B cell population with antibodies directed against a swathe of CNS proteins.
Gesehen am 15.12.2025